Contemporary management - Jones, Gareth R. (McGraw-Hill/Irwin, 2011)
Contemporary Management is a comprehensive text that surveys the theoretical underpinnings of modern management thought and research. Through a variety of examples from an expanded number of small business to medium and large companies it shows the reader how those ideas are used by practicing managers. A hallmark of this text is its focus on the “Manager as a Person,” which discusses managers as real people with their own personalities, strengths, weaknesses, opportunities, and problems.